2022
DOI: 10.1364/josaa.476795
|View full text |Cite
|
Sign up to set email alerts
|

Tikhonov regularization-based extended Kalman filter technique for robust and accurate reconstruction in diffuse optical tomography

Abstract: Diffuse optical tomography (DOT) is a non-invasive imaging modality that uses near-infrared light to probe the optical properties of tissue. In conventionally used deterministic methods for DOT inversion, the measurement errors were not taken into account, resulting in unsatisfactory noise robustness and, consequently, affecting the DOT image reconstruction quality. In order to overcome this defect, an extended Kalman filter (EKF)-based DOT reconstruction algorithm was introduced first, which improved the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Baez [ 15 ] et al employed extended Kalman filtering (EKF) algorithm to estimate DOT image, and the results showed that the EKF-based method can effectively improve noise robustness compared with the NIRFAST solver (LM algorithm). In our group, Zhang [ 16 ] et al proposed a regularization-based EKF algorithm for DOT reconstruction, where Tikhonov regularization was incorporated to EKF process, resulting in superior imaging accuracy and noise robustness, especially under the circumstance of low absorption contrast and high noise level, compared with the conventional algebraic reconstruction technique (ART) and L2 regularization. Briefly, the strength of nonlinear filtering method is that it takes into account the influence of measurement noise on the filtering results during the iteration process, and thus the accuracy and noise robustness of image reconstruction can be improved to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Baez [ 15 ] et al employed extended Kalman filtering (EKF) algorithm to estimate DOT image, and the results showed that the EKF-based method can effectively improve noise robustness compared with the NIRFAST solver (LM algorithm). In our group, Zhang [ 16 ] et al proposed a regularization-based EKF algorithm for DOT reconstruction, where Tikhonov regularization was incorporated to EKF process, resulting in superior imaging accuracy and noise robustness, especially under the circumstance of low absorption contrast and high noise level, compared with the conventional algebraic reconstruction technique (ART) and L2 regularization. Briefly, the strength of nonlinear filtering method is that it takes into account the influence of measurement noise on the filtering results during the iteration process, and thus the accuracy and noise robustness of image reconstruction can be improved to some extent.…”
Section: Introductionmentioning
confidence: 99%